Changes in Intensity of Physical Exercise as Predictors of Depressive Symptoms among Older Adults: An Eight-Year Follow-Up - Lampinen, Päivi; Heikkinen, Riitta-Liisa; Ruoppila, Isto (Preventive medicine, 2000)
Background. Epidemiological research suggests that regular physical activity may be associated with reduced depressive symptoms. The present study examines the predictive value of physical exercise in relation to depressive symptoms among samples of adults aged 65+ during an 8-year period. Methods. The subjects (N = 663) who participated both at the baseline (1988) and the follow-up (1996) interviews were selected for the analyses. The dependent variable depressive symptoms was assessed by the Finnish modified version of Beck's 13-item depression scale. The independent variable was the intensity of physical exercise. Results. The intensity of physical exercise decreased among the older men and women. Those who had reduced their intensity of physical exercise during the 8 years reported more depressive symptoms at the follow-up than those who had remained active or in creased their physical activity. Depressive symptoms were predicted by the intensity of baseline physical exercise, earlier depressive symptoms, older age, gender, having three or more chronic somatic conditions, and difficulties in performing ADL activities. Conclusions. Age-related decrease in the intensity of physical exercise increases the risk of depressive symptoms among older adults. This calls for effective measures in maintaining and supporting an adequate level of physical exercise among the aging population.